Standardization of seed viability testing through tetrazolium in oil palm (Elaeis guineensis L.): Standardization of seed viability testing through tetrazolium in oil palm (Elaeis guineensis L.) - G RAVICHANDRAN; B KALYANA BABU; P ANITHA; G SOMASUNDARAM; H P BHAGYA (Journal of Oilseeds Research, 2020)
To evaluate the seed viability in the zygotic embryo of oil palm through quick test, different tetrazolium (TZ) concentrations, staining temperatures, staining timings and staining pattern were evaluated in the Dura x Pisifera (D x P) crossed seeds. The best staining was obtained with 1 % TZ solution under 30oC for 5 hours kept under complete dark. The staining pattern on the embryo indicated that the top portion towards the operculum had given proper growth in vitro. Hence, TZ staining was found suitable indicator for seed viability in oil palm seed.